2015
DOI: 10.1371/journal.pone.0123323
|View full text |Cite
|
Sign up to set email alerts
|

Is Urinary Lipoarabinomannan the Result of Renal Tuberculosis? Assessment of the Renal Histology in an Autopsy Cohort of Ugandan HIV-Infected Adults

Abstract: ObjectiveThe detection of urinary lipoarabinomannan (LAM), a mycobacterial cell wall component, is used to diagnose tuberculosis (TB). How LAM enters the urine is not known. To investigate if urinary LAM-positivity is the result of renal TB infection we correlated the outcomes of urinary LAM-antigen testing to renal histology in an autopsy cohort of hospitalized, Ugandan, HIV-infected adults.MethodsWe performed a complete autopsy, including renal sampling, in HIV-infected adults that died during hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…As replicating Mtb degrades, LAM circulating in the blood is filtered across the glomerular basement membrane of the kidneys into urine (Figure 1). The presence of LAM in urine can also be a result of renal Mtb infection, as has been shown in autopsy studies [16]. Table 1.…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 77%
See 1 more Smart Citation
“…As replicating Mtb degrades, LAM circulating in the blood is filtered across the glomerular basement membrane of the kidneys into urine (Figure 1). The presence of LAM in urine can also be a result of renal Mtb infection, as has been shown in autopsy studies [16]. Table 1.…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 77%
“…There is evidence that HIV/TB co-infected patients with immunosuppression and disseminated TB have higher LAM concentrations in their urine [37]. Biological mechanisms to explain this are not fully understood; whether this is due to an overall higher bacterial body burden or renal TB infection is unclear [16,38]. While HIV co-infection or urinary tract disease are not necessary for LAM antigenuria, they both can lead to higher urine LAM concentrations.…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
“…Cox et al demonstrated histological evidence of renal TB in the majority of deceased patients with LAM detected in their urine. 17 All LAM-positive patients had evidence of either renal or disseminated TB. Renal TB is also frequently found in cadavers of adults with disseminated TB at post-mortem, typically being seen in more than 50% of such cases.…”
Section: Evidence Of Renal Tb From Post-mortem Studiesmentioning
confidence: 97%
“… 14 Whilst glomerular dysfunction might hypothetically allow LAM-containing-complexes to pass into the urine, clinical studies have not found associations between urine-LAM detection and proteinuria (a marker for glomerular damage), 15 , 16 and there is no histological evidence of glomerular damage at autopsy in patients who were urine-LAM positive. 17 …”
Section: Simple Filtration Of Lam At the Renal Glomerulus Is Implausimentioning
confidence: 99%
“…The Determine TB LAM Ag test (Determine TB-LAM Ag test, Abbott, Waltham, MA, USA [formerly Alere]; LAM test) is a lateral flow assay for urinary Lipoarabinomannan (LAM) that can detect active TB within 30 min. LAM is useful in HIVpositive individuals with advanced immunodeficiency [5,6]. The World Health Organization (WHO) currently recommends the use of the LAM test to assist in the diagnosis of TB in HIVpositive patients with CD4 counts less than or equal to 100 cells/µl or in severely ill HIV-positive patients, regardless of the CD4 count, or in those with an unknown CD4 count [7].…”
Section: Introductionmentioning
confidence: 99%